Pruning waste versus circular economy: a case study - Levandoski, Ana Paula; Trentin, Fernanda; Favretto , Jacir; Guimarães Filho , Leopoldo Pedro; Bristot, Vilson Menegon; Reis, Mari Aurora Favero (Brazilian Journal of Production Engineering, 2024)
The management of urban solid waste is most discussed when it comes to contaminating waste, but little is discussed about sustainability in the urban management of pruning waste. The objective of the study is to identify the demand and destination of waste from tree and shrub pruning in the city of Concórdia, SC. The study has a qualitative and quantitative approach, exploratory and descriptive. The data was collected in a spreadsheet, from January to September 2019. Based on the data presented by the company providing the service in the city of Concórdia, it was possible to carry out a daily and monthly analysis of the collections in the period. The results showed that the months with the highest amount of pruning were May, June, and July, demonstrating that it was a winter pruning harvest, with a daily average of 4 tons/day. The analysis shows the challenges in collection and disposal. This material is destined for landfill, but it can be used as raw material in production systems, such as energy production. Also, the study shows the need to develop environmental education programs to reduce the amount of pruning waste in the city.
Keywords: Pruning residues; afforestation; urban vegetation; sustainability.